Semiclassical Theory for Low Density Properties of Polar Hard D-Sphere Fluid Mixtures - Kumar, Shyambhu; Yadav, Ranjit Prasad (Academic Voices: A Multidisciplinary Journal, 2016)
In the present paper, expansions are obtained for density-independent pair distribution function and second virial coefficient for D-dimensional molecular fluid mixtures of dipolar hard D-spheres in the semiclassical limit. Numerical results for the second virial coefficient are also estimated for binary mixture of (i) hard spheres and dipolar hard spheres and (ii) hard discs and dipolar hard discs. It is found that the quantum effects increase with increase of dipole moment μ2 as well as the concentration x2. The purpose of the present work is to develop a theory for calculating the low density properties of the polar hard D-sphere fluid mixture in the semiclassical limit. We have also developed the theory for estimating the quantum corrections to the density independent pair distribution function (PDF) and second virial coefficient of the polar D-sphere fluid mixtures. Academic Voices Vol.5 2015: 48-55